2023
DOI: 10.3390/microorganisms11020472
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Metabolome Changes in Three Pulmonary Hypertension Rat Models

Abstract: Dysbiosis of the gut microbiota and metabolites is found in both pulmonary hypertension patients and pulmonary hypertension rodent models. However, the exact changes in gut microbiota during the development of pulmonary hypertension is unclear. The function of the gut microbiota is also ambiguous. Here, this study showed that the gut microbiota was disrupted in rats with hypoxia (Hyp)-, hypoxia/Sugen5416 (HySu)-, and monocrotaline (MCT)-induced pulmonary hypertension. The gut microbiota is dynamically changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…While we did not assess whether the protective effect of soluble-fiber in HPH was dependent on SCFA production, in the deoxycortisone acetate-salt mouse model of systemic hypertension, the protective effect of dietary-fiber was phenocopied by treatment with the SCFA acetate, 7 propionate supplementation has been shown to protect against angiotensin II-induced systemic hypertension, 40 and butyrate has been shown to protect against HPH in rats. 41 In addition to the SCFA-promoting effects of the HSFiD, in hypoxic mice we found that the lack of soluble-fiber increased the abundance of Romboutsia , Clostridioides , and Streptococcus— 3 genera that have been shown to be elevated in rodent models of PH, 42 partially overlap with genera that are enriched in PAH and chronic obstructive pulmonary disease patients, 14,43 and are associated with inflammation. These data suggest a detrimental effect of LSFiD.…”
Section: Discussionmentioning
confidence: 74%
“…While we did not assess whether the protective effect of soluble-fiber in HPH was dependent on SCFA production, in the deoxycortisone acetate-salt mouse model of systemic hypertension, the protective effect of dietary-fiber was phenocopied by treatment with the SCFA acetate, 7 propionate supplementation has been shown to protect against angiotensin II-induced systemic hypertension, 40 and butyrate has been shown to protect against HPH in rats. 41 In addition to the SCFA-promoting effects of the HSFiD, in hypoxic mice we found that the lack of soluble-fiber increased the abundance of Romboutsia , Clostridioides , and Streptococcus— 3 genera that have been shown to be elevated in rodent models of PH, 42 partially overlap with genera that are enriched in PAH and chronic obstructive pulmonary disease patients, 14,43 and are associated with inflammation. These data suggest a detrimental effect of LSFiD.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, the variability of α-diversity in the HySu rats was similar to the group given MCT. This may indicate similarities of the gut microbiota in PAH type 1 and PAH type 3 [16].…”
Section: Changes In the Gut Microbiota Composition In Pahmentioning
confidence: 88%
“…Compared to healthy controls, MCT‐induced rats exhibited an increased F/B ratio, and several pathogenic species, including Clostridium , Turicibacter , and Mollicutes genera, were predominant [ 116 ]. Actinobacteria, Firmicutes, Proteobacteria abundance increased, and Spirochaetota, Bacteroidetes, unidentified bacteria, and Verrucomicrobi decreased [ 117 , 118 ].…”
Section: Gut Microbiota Profiles Of Phmentioning
confidence: 99%